2020
DOI: 10.48550/arxiv.2003.05950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Link Between Ram Pressure Stripping and Active Galactic Nuclei

Angelo Ricarte,
Michael Tremmel,
Priyamvada Natarajan
et al.

Abstract: The dense environment of a galaxy cluster can radically transform the content of in-falling galaxies. Recent observations have found a significant population of active galactic nuclei (AGN) within "jellyfish galaxies," galaxies with trailing tails of gas and stars that indicate significant ram pressure stripping. The relationship between AGN and ram pressure stripping is not well understood. In this letter, we investigate the connection between AGN activity and ram pressure in a fully cosmological setting for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
2
Order By: Relevance
“…Moreover, a long-lasting and population-averaged environmental obstruction to AGN activity is not necessarily in contrast to previous findings which have shown that higher density cluster environments can actually trigger enhanced BH activity in satellites for a period of time, which in some instances can in turn act to eventually quench the satellites (e.g. McGee 2013;Poggianti et al 2017;Ricarte et al 2020).…”
Section: On the Role Of Massive Hosts And Of Agn Feedback In Massive ...contrasting
confidence: 62%
“…Moreover, a long-lasting and population-averaged environmental obstruction to AGN activity is not necessarily in contrast to previous findings which have shown that higher density cluster environments can actually trigger enhanced BH activity in satellites for a period of time, which in some instances can in turn act to eventually quench the satellites (e.g. McGee 2013;Poggianti et al 2017;Ricarte et al 2020).…”
Section: On the Role Of Massive Hosts And Of Agn Feedback In Massive ...contrasting
confidence: 62%
“…Our findings appear to be in contrast to previous studies that have concluded that higher density cluster environments actually trigger enhanced BH activity in satellites for a period of time, which in turn acts to eventually quench the satellites (e.g. see McGee 2013;Poggianti et al 2017;Ricarte et al 2020). However, it should be kept in mind that the results shown in Fig.…”
Section: The Role Of Agn Feedbackcontrasting
confidence: 99%
“…Can observations of the dynamics of the gas in the disk in high resolution help us to explain the elevated incidence of AGN in ram pressure affected galaxies observed by Poggianti et al (2017b)? Some simulations support that ram pressure stripping can drive gravitationally bound gas inward, accelerating black hole accretion rates and possibly triggering AGN (Tonnesen & Bryan 2009;Ramos-Martínez et al 2018;Ricarte et al 2020).…”
Section: Introductionmentioning
confidence: 99%